Efficient Time-Domain Ray-Tracing Technique for the Analysis of Ultra-Wideband Indoor Environments including Lossy Materials and Multiple Effects - F. Saez de Adana; O. Gutiérrez; M. A. Navarro; A. S. Mohan (International Journal of Antennas and Propagation)
This paper presents an efficient application of the Time-Domain Uniform Theory of Diffraction (TD-UTD) for the analysis of Ultra-Wideband (UWB) mobile communications for indoor environments. The classical TD-UTD formulation is modified to include the contribution of lossy materials and multiple-ray interactions with the environment. The electromagnetic analysis is combined with a ray-tracing acceleration technique to treat realistic and complex environments. The validity of this method is tested with measurements performed inside the Polytechnic building of the University of Alcala and shows good performance of the model for the analysis of UWB propagation.